Diplomatic-Domestic Paradox of Indonesian Autonomous Weapons: A Sui Generis Regulatory Model for the KSOT Submarine System - Sugiarto; Linus Yoseph Wawan Rukmono; Tivensandro Tivensandro (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
The development of artificial intelligence-based Autonomous Weapons Systems (AWS) has created significant legal and ethical challenges, particularly for an archipelagic nation like Indonesia, which is modernizing its maritime defense. This study aims to analyze the suitability of AWS use with the principles of Just War Theory, identify regulatory gaps in Indonesian defense law, and formulate an accountable regulatory model. This study employs a normative juridical method, drawing on legislative, conceptual, and comparative approaches. The results show that Indonesia faces a domestic-diplomacy paradox, where Indonesia internationally supports AWS restrictions, but domestically develops systems such as the KSOT-008 autonomous submarine within an inadequate legal framework. Law Number 3 of 2002 and Law Number 3 of 2025 do not explicitly regulate the limits of AWS autonomy and accountability mechanisms, particularly in Military Operations Other Than War, which may create an accountability gap. Furthermore, the limitations of acoustic communication in the underwater domain limit the application of meaningful human control. To address these issues, this study recommends a sui generis regulatory model that includes a ban on fully autonomous systems, expanded command responsibility through the concept of algorithmic mens rea, recognition of institutional responsibility, and the establishment of a national oversight mechanism. This model is expected to ensure that the use of AWS remains in line with the principles of international humanitarian law, legal accountability, and the supremacy of national law.